ANALYSIS OF SPECIFIC SRATEGY OF THE 200M AND 400M INDIVIDUAL MEDLEY SWIMMERS IN THE 45th THAILAND NATIONAL GAME - Chainok, Phornpot; Nakkanueng, Hamdan; Sowhasun, Irin; Matjiur, Radomyos (Journal of Sports Science and Health, 2020)
Purposes : The purpose of this study were to study and compare specific pacing strategy between male and female swimmers and to find the correlations between swimming characteristics and 200m and 400m individual medley swimming performance at the 45th Thailand national game. Methods : The performance of the sixteen finalist swimmers (M = 8, F = 8) competing in 200m and 400m IM events in the 45th Thailand national game was filmed at 50 Hzs and analyzed using the Dartfish software. Independent t-test was conducted to evaluate any differences in pacing strategy between male and female swimmers and a multiple linear regression was used to create the predicted equation of 200m and 400m IM swimming performance. Statistical significance was set at p ≤ 0.05. Results : The specific pacing strategy pattern of the 200m and 400m IM swimming were similar between male and female swimmers, with a greater average swimming velocity in male than in female. The swimming velocity was the highest in butterfly, followed by freestyle, backstroke and breaststroke, respectively. The average of swimming velocity and stroke rate (SR) were significantly greater (p <0.05) in 200m than in 400m distances. In addition, The SR increases proportionately with stroke index (SI). On the contrary, stroke length (SL) increased as SR decreased. The SI was significantly greater (p <0.05) in 200m than that in 400m. The prediction equation was velocity = –0.313 + (0.549* FR speed) + (0.551* turning velocity of BU to BA) for 200m IM and was velocity = –0.010 + (0.337* BU speed) + (0.294* BA speed) + (0.250* FR speed) + (0.035* stroke index of BR) for 400m IM. Conclusion : The analysis of specific pacing strategy of the 200m and 400m IM swimming events showed a similar pattern between male and female swimmers, with the highest velocity observed in butterfly and lowest in breaststroke. The multiple linear regression analysis revealed the key factors in predicting swimming performance of 200m and 400m IM, which can be used for designing specific training program for each swimmer.